Tourist Language Learning: A Way of Grasping Human Interaction (KULT_online, 2009)
Learning the Arts of Linguistic Survival: Languaging, Tourism, Life represents a critical analysis of the motivation for as well as nature and impact of human interaction in multilingual and multicultural tourist language-learning settings. This is approached from a variety of disciplinary perspectives, including modern languages education, anthropology, linguistics, and sociology as well as tourism and intercultural and literary studies. Commencing with an identification of “commonplaces of language pedagogy, communicative learning and intercultural communicative competence” (p. 2) in chapters 1 and 2, this monograph further invites and encourages readers to travel, both imaginatively and physically, through various dimensions of tourist language learning. Thus, chapters 3 through 9 are dedicated to instances of risk, way finding and the following of directions, pronunciation, conversations, games, speech rehearsal, and the concept of “breaking English”. The final two chapters provide an in-depth recapitulation of the “gains and pains” of tourist language learning as forms of the human need for survival.